Pengaruh Aksebilitas, Promosi Dan Jaminan Rasa Aman Terhadap Keputusan Pembelian Konsumen Pada Toko Make Over Transmart Padang - Maria Magdalena; Jeki Algusri; Qori Rizqia (Universitas 45 Surabaya, 2024)
Consumer purchasing decisions are a process where consumers choose and evaluate products or services, consumers often consider various things that suit their needs in the purchasing decision process. This research aims to test whether accessibility, promotion and security guarantees influence purchasing decisions for Transmart Padang make overs. The data source used in this research is primary data. The population in this observation was Transmart visitors, totaling 2,230 people. This sampling technique is slovin. The number of samples used in this research was 96 people. The analytical method used is multiple regression analysis. The conclusion of this research is that Accessibility (X1) has a positive and significant effect on purchasing decisions, Promotion (X2) has a positive and significant effect on purchasing decisions and Security Guarantee has a positive and significant effect on purchasing decisions.